Biological Characterstics Of Buffaloes Hydatid Cysts: R H Rahif , M A-A Al-Fetlawi - Rahif, R. H. (The Iraqi Journal of Veterinary Medicine, 2005)
Hydatid cysts infection rate was 13.56% in buffaloes, slaughtered at Al-Diwania abbatoir, Al-Qaddisia province,Iraq, during the time period from July,2000 to June, 2001.The only infected animals were the females, and the higher rateof infection was found in those aged buffaloes. Lungs,livers, livers and lungs wereinfected with 50%, 37.5% and 12.5%, respectively. The total rate of hydatid cystsfertility was 53.85%, and the sterile, caseated and calcified cysts were 23.08%, 11,54% and 11.5%, respectively. The mean total rate of viability of protoscoleces was73.91%, and that of livers and lungs protoscoleces were 82.62% and 70.60%.Results denoted that the numbers of protoscoleces was increased proportionallywith size of their cysts, and in contrary to that the viability of protoscolecesdiminished with the increase size of cysts. The study concluded that buffaloes havean important role in maintaining the life cycle and epidemiology of Echinococcusgranuolosus in dogs in those areas where buffaloes are raised, and this is incontroversy with the claims of previous authors.